Seni Terapi Air - Yedi Purwanto (Jurnal Sosioteknologi, 2008)
This paper discusses one of the water uses i.e. as an alternative medicine for human. The use of water for medicine is supported not only by the research findings on the water used for medicine conducted by Masaru Emoto but also by some verses in Al-Qur'an (Islamic holy book) and some haditshs (statements) of the prophet Muhammad.